3(5x+6)+5(3x+3)+3=30x+37

Simple and best practice solution for 3(5x+6)+5(3x+3)+3=30x+37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x+6)+5(3x+3)+3=30x+37 equation:


Simplifying
3(5x + 6) + 5(3x + 3) + 3 = 30x + 37

Reorder the terms:
3(6 + 5x) + 5(3x + 3) + 3 = 30x + 37
(6 * 3 + 5x * 3) + 5(3x + 3) + 3 = 30x + 37
(18 + 15x) + 5(3x + 3) + 3 = 30x + 37

Reorder the terms:
18 + 15x + 5(3 + 3x) + 3 = 30x + 37
18 + 15x + (3 * 5 + 3x * 5) + 3 = 30x + 37
18 + 15x + (15 + 15x) + 3 = 30x + 37

Reorder the terms:
18 + 15 + 3 + 15x + 15x = 30x + 37

Combine like terms: 18 + 15 = 33
33 + 3 + 15x + 15x = 30x + 37

Combine like terms: 33 + 3 = 36
36 + 15x + 15x = 30x + 37

Combine like terms: 15x + 15x = 30x
36 + 30x = 30x + 37

Reorder the terms:
36 + 30x = 37 + 30x

Add '-30x' to each side of the equation.
36 + 30x + -30x = 37 + 30x + -30x

Combine like terms: 30x + -30x = 0
36 + 0 = 37 + 30x + -30x
36 = 37 + 30x + -30x

Combine like terms: 30x + -30x = 0
36 = 37 + 0
36 = 37

Solving
36 = 37

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8x-1=9x-5 | | 39(x+4)=5x+16 | | 5-2y=3x | | 118.8-7.7x=3.3+39.6 | | 8=-5y-2 | | 2/3-7= | | -5n+x=78 | | 8(2n-3)=(2n+8)+3 | | 5x+5x+4+8=7x+4+2x | | -3(t+4)=3 | | 3(2-z)*0.2=z | | (3x)+4=-11 | | 11(2+8x)-10(10-11x)=912 | | -2(x-18)=(-x/2+3)(-3) | | 12=4n-10 | | x^3=216 | | -5=-x+3 | | 6x+2+3x+17=10 | | 3n+6n=3-9 | | .6a-.75b=c | | 7(-2x+6)=126 | | 5a^2+20a+3=0 | | -3q+4=q | | 3(3x+4)+3(3x+4)=18x+30 | | 7x+4+4x+9=10x+3 | | 3(x+7)-3(x+2)=36 | | 6y^2+9y=11y-4 | | 4v^2-28v+49=0 | | 3(x+7)-3(x+2)=-36 | | 6+8(x-9)=9-3(x-9) | | z-5=7z-9-z | | x-6=7x |

Equations solver categories